Pattern of Dermatosis Among the Admitted Neonates in A Tertiary Care Hospital (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background: Neonatal dermatosis are common in neonatal period of first twentyeight days. Most of which are physiological, transient and require no therapy, aswell as pathological lesions in the skin of neonates. This study was done to see thepattern of dermatosis in neonates and to establish the correlation between variousneonatal factors, maternal factors and the occurance of dermatosis and to identifythem correctly to avoid concerns of parents, Gynaecologist and Pediatricians.Materials and methods: A total of 1000 admitted neonates in a 4 month period inneonatal ward of a tertiary care hospital were included in this study and a detailedhistory and dermatological examination including hair , nail and mucous membraneof each neonate was carried out. Laboratory procedures were performed asrequired.Results: We found 300 (30%) newborns had one or more skin lesions out of 1000newborns examined. Male to female ratio was 1.14:1. Most common skin changesobserved was physiological scaling (50%), Acne neonatorum (13%), Erythematoxicum neonatorum (11%), Xerosis (10%), Milia (9%), Cutis marmorata (7%),Infantile seborrhoic dermatitis (7%). Among congenital skin lesions, congenitalmelanocytic nevus (1%) portwine stain (1%). Genodermatosis are Epidermolysisbullosa (0.3%), Congenital icthyosiform erythroderma (0.3%). Acquired skinmanifestation seen in 17% of cases.Conclusions: Neonates are prone to suffer from a different varieties of dermatosisboth physiological and pathological which are unique to neonates. It is important todifferentiate them from other serious skin conditions which shows the importance ofa dermatologist in the neonatal unit of a hospital.Chatt Maa Shi Hosp Med Coll J; Vol.19 (1); January 2020; Page 15-19